Internal banking security in the events of Anti-Money Laundering - I. A. Krestovskiy (Путеводитель предпринимателя, 2020)
The main problem of banks today is the theft committed by ordinary operational staff (fraud in cash with customers, withdrawing money from depositors’ accounts without their knowledge, conducting illegal operations withforeign currency, embezzling cash, etc.). To disclose and suppress the aforementioned bank crimes, employees ofdepartments (sectors) of internal banking security do not need to have a special economic education and know all the subtleties of conducting banking operations. If it is necessary to stop abuses in the field Money Laundering, the fact of working in the police will clearly not be enough.